2009
DOI: 10.1002/eji.200838863
|View full text |Cite
|
Sign up to set email alerts
|

Statins inhibit NK‐cell cytotoxicity by interfering with LFA‐1‐mediated conjugate formation

Abstract: Inhibitors of the 3-hydroxy-3-methylglutaryl coenzyme A reductase, commonly referred to as statins, are inhibitors of cholesterol biosynthesis. They are broadly used for treating hypercholesterolemia and for prevention of cardio-and cerebrovascular diseases. Recent publications show that statins also act as immunomodulatory drugs. Here, we show that lipophilic statins inhibit NK-cell degranulation and cytotoxicity. This effect was reversible by addition of substrates of isoprenylation, but not by addition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
1
34
0
2
Order By: Relevance
“…Statins have been shown to increase regulatory T-cell numbers and functionality in vivo [45,46]; both lipophilic and hydrophilic statins decrease natural killer cell cytotoxicity [47,48]. These immunosuppressive effects of statins might impair host antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been shown to increase regulatory T-cell numbers and functionality in vivo [45,46]; both lipophilic and hydrophilic statins decrease natural killer cell cytotoxicity [47,48]. These immunosuppressive effects of statins might impair host antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of statins on NK cells reported so far were all inhibitory (9)(10)(11)(12). In all these studies, which focused on NK celltarget cell interactions, purified NK cells were used in coculture with target cells but the role of APCs had not been investigated at all.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that statins are predominantly anti-inflammatory and immunosuppressive agents, an increasing number of studies have shown that statins may also induce proinflammatory responses depending on costimulatory signals (5)(6)(7)(8). In contrast, with regard to NK cells, only inhibitory effects have been reported so far (9)(10)(11)(12). However, all these studies focused on NK cell-target cell interactions but did not investigate the role of antigen-presenting cells (APC) in statin-mediated NK cell modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, statins have been shown to increase regulatory T-cell numbers and functionality in vivo [41][42][43]. Both lipophilic and hydrophilic statins decrease natural killer cell cytotoxicity [44]. These immunosuppressive effects of statins might impair host antitumour immune responses, suggesting an opposing effect on tumour development, which should be considered.…”
Section: Figurementioning
confidence: 99%